RESISTÊNCIA À CORTICOTERAPIA E SUA RELAÇÃO COM PROTEÍNAS PODOCITÁRIAS ALTERADAS NA SÍNDROME NEFRÓTICA - Cotrim de Macedo, Lara; Duarte Malta, Marcella; Maia Wanderley Júnior, Rommel; Couto de Albuquerque Melo, Vinícius; Pinto, Ana Paula (SEMPESq - Semana de Pesquisa da Unit - Alagoas, 2020)
INTRODUÇÃO: A síndrome nefrótica é definida pela ocorrência de albuminúria superior a 3-3,5 g/ dia, acompanhada de hipoalbuminemia, edema e hiperlipidemia. Existem vários casos de síndrome nefrótica em adultos, dentre elas a doença por lesão mínima, a glomeruloesclerose focal segmentar, a nefropatia membranosa e a glomerulonefrite membranoproliferativa. Nesse trilhar, estima-se que 10 a 20% das crianças com síndrome nefrótica idiopática (SNI) são córtico-resistentes. OBJETIVOS: O objetivo deste trabalho consiste em conhecer clinicamente os pacientes com síndrome nefrótica resistentes à corticoterapia. MATERIAL E MÉTODO: Foram selecionados artigos nos seguintes bancos de dados: Uptodate, SciELO e KDIGO, que abordassem sobre a resistência a corticoterapia nos pacientes com síndrome nefrótica. RESULTADO E DISCUSSÃO: A incidência correta de síndrome nefrótica idiopática córtico-resistente (SNICR) ainda é incerta, uma vez que não existe homogeneidade na sua definição. Segundo o Estudo internacional da doença renal em criança (ISKDC), os pacientes córtico-resistentes são aqueles que não respondem ao tratamento com prednisona durante as primeiras 8 semanas. Já a sociedade francesa de nefrologia classifica como resistentes aqueles que não respondem após o tratamento de 4 semanas com corticoide. De modo diferente, a diretriz da Kidney Disease Improving Global Outcomes sugere o mínimo de 8 semanas tratamento com corticoide para definir resistência aos corticoides; além disso, para avaliar uma criança com SNICR é necessária a realização de biópsia renal, análise da função renal por taxa de filtração glomerular (TFG) e quantificação da excreção de proteína na urina. Na maioria das crianças SNICR, a causa subjacente não é conhecida. Entretanto, na atualidade, sabe-se que defeitos únicos do gene que afetam a diferenciação e a função dos podócitos glomerulares são responsáveis por um terço de todos os casos pediátricos de SNICR em diversas partes do mundo. As mutações mais comuns ocorrem nos genes: NPHS1, que codifica a nefrina; NPHS2, que codifica a podocina; e o WT1, que codifica a proteína supressora de tumor de transcrição, que está relacionada ao desenvolvimento de rins e gônadas. A nefrina e a podocina compõem os podócitos.CONCLUSÃO: Os pacientes que apresentam SNICR tem risco aumentado de complicações, como desnutrição, hiperlipidemia, fenômenos tromboembólicos e progressão para doença renal terminal. Portanto, para evitar estas comorbidades, a metodologia mais aceita para reconhecimento destes indivíduos consiste na não melhoria do quadro clínico após 8 semanas de tratamento com corticoide conforme as diretrizes da KDIGO. Palavras-chave: Corticoresistencia, doença de lesão mínima, podócitos ABSTRACT: INTRODUCTION: Nephrotic syndrome is defined as the occurrence of albuminuria exceeding 3 to 3.5 g/day, combined with hypoalbuminemia, edema and hyperlipidemia. There are several cases of nephrotic syndrome in adults, among them minimal lesion disease, focal segmental glomerulosclerosis, membranous nephropathy and membranoproliferative glomerulonephritis. About 10 to 20% of children with idiopathic nephrotic syndrome (INS) are corticoid-resistant. However, the incidence of idiopathic corticoid-resistant nephrotic syndrome (SNICR) is still uncertain, since there is no consensus in its definition. For example, according to the International Kidney Disease Study in Children (ISKDC), corticoid-resistant patients are those who do not respond to treatment with prednisone for the first 8 weeks. For the French Nephrology Society, it classifies as resistant those who do not respond after the 4-week treatment with corticosteroids. Differently, the Kidney Disease Improving Global Outcomes (KDIGO) guideline suggests a minimum of 8 weeks corticosteroid treatment to define resistance to corticosteroids; in addition, a renal biopsy, kidney function test by glomerular filtration rate (GFR) and quantification of protein excretion in the urine are required to evaluate a child with SNICR. OBJECTIVES: The general objective is to know patients with nephrotic syndrome resistant to corticoids. The specifics objectives includes the expansion of knowledge within the different definitions of resistance, the possible genes involved with resistance, as well as to correlate such genes with podocyte proteins. MATERIAL AND METHOD: Articles that approached the resistance to corticosteroid therapy in patients with nephrotic syndrome were selected in the following databases: Uptodate, SciELO and KDIGO. RESULTS AND DISCUSSION: However, the incidence of idiopathic corticoid-resistant nephrotic syndrome (SNICR) is still uncertain, since there is no consensus in its definition. For example, according to the International Kidney Disease Study in Children (ISKDC), corticoid-resistant patients are those who do not respond to treatment with prednisone for the first 8 weeks. For the French Nephrology Society, it classifies as resistant those who do not respond after the 4-week treatment with corticosteroids.Differently, the Kidney Disease Improving Global Outcomes (KDIGO) guideline suggests a minimum of 8 weeks corticosteroid treatment to define resistance to corticosteroids; in addition, a renal biopsy, kidney function test by glomerular filtration rate (GFR) and quantification of protein excretion in the urine are required to evaluate a child with SNICR.In most SNICS children, the underlying cause is unknown. However, it is known that single gene defects affecting differentiation and function of the glomerular podocytes account for one-third of all pediatric cases of SNICR in various parts of the world. The most common mutations occur in the genes: NPHS1, which encodes nephrin; NPHS2, which encodes the podocin; and WT1, which encodes the transcription tumor suppressor protein, related to the development of kidneys and gonads. Nephrine and pocodin compound the podocytes. CONCLUSION: Thus, patients with NRTIs, on the other hand, have an increased risk of complications such as malnutrition, hyperlipidemia, thromboembolic phenomena and progression to end-stage renal disease. Thus, the most accepted form currently consists of not improving the clinical picture of the patient after 8 weeks of treatment with corticosteroids according to KDIGO guidelines. Keywords: Corticoresistency, minimal lesion disease, podocytes